Teaching English for Management: A Perspective of Pragmatics - I Nengah Laba (Denpasar Institute, 2022)
This paper aims to analyse the application of pragmatic theory and principles to the teaching of English for management. The research is conducted through a qualitative research design, using a combination of case study and classroom observations. The data collected will be analyzed using a descriptive-qualitative methods, including thematic analysis. The teaching of English for management from a pragmatics perspective provide students with a comprehensive understanding of the use of language in a business context, and equip them with the skills and knowledge they need to communicate effectively in a global business environment. The integration of pragmatics into the teaching of English for management enhance the students' critical thinking skills. It is also found out that a pragmatics-based approach to teaching English for management is taught in conjunction with other aspects of language learning, such as grammar, vocabulary, and pronunciation. The findings of this study have important implications for the development of English language teaching in business context. The results of this study suggest that the integration of pragmatics into the teaching of English for management can enhance students' communication skills.